Hazard assessment of GLOFs from moraine-dammed lakes and related debris-flows - Emmer, Adam (2016)
Original abstract: Glacial lake outburst floods (GLOFs) from moraine-dammed lakes and related debris-flows represent a significant threat in high mountainous areas across the globe. It is necessary to quantify this threat so as to mitigate against their catastrophic effects. Three approaches are used in GLOF hazard assessment: (1) qualitative; (2) semi-quantitative; and (3) quantitative. Each has specific advantages and disadvantages. Based on a search of the scientific literature, this paper summarises the various methods of GLOF hazard assessment and outlines their application.